Australia's next-generation Autonomous Underwater Vehicle for Antarctic research - Damien Guihen; Konrad Zurcher; Isak Bowden-Floyd; Peter King; Vanessa Lucieer (2016)
The Antarctic Gateway Partnership has been funded to advance the Australian capacity to undertake Antarctic science and is both improving the understanding of the physical and ecological environment and is building the facilities for the next-generation of Antarctic research. A crucial component of the Partnership is the development of a high specification, multi-sensor polar Autonomous Underwater Vehicle. A key finding of SCAR’s recent Horizon Scanning exercise was the prominent role that Autonomous Underwater Vehicles (AUV) will play in answering the big questions facing Antarctic science. These big questions, including the mechanics of sea-ice formation, water column processes and ecosystem dynamics, drive the engineering and scientific focus of the AUV’s development. Multiple sensor suites, such as a current profiler, side-scan sonar and hyper-spectral camera will complement the collection of physical samples using a sediment corer and a water sampler. Making manifold, simultaneous and diverse observations from a platform that can travel through the water column, to the seabed or under ice has the potential to support a wide array of important multidisciplinary Antarctic research. We will present our vision for this new facility along with an update on its development and will lay out the deployment options for the vehicle and how it will enable researchers to investigate processes that have to date been too difficult to access or to sample over wide temporal and spatial scales. We will discuss sensor readiness, future missions and the benefit that the international community can gain from Australia’s next-generation polar AUV.